Synthesis and utilization of biomass-derived sulfonated heterogeneous catalyst-BT-SO3H for microalgal biodiesel production - Ao, Supongsenla; Rashid, Umer; Shi, Da; Rokhum, Samuel Lalthazuala; TG Thuy, Le; Awad Alahmadi, Tahani; Chinnathambi, Arunachalam; Mathimani, Thangavel (Elsevier, 2024)
The study investigates the potential of utilizing banana trunk-derived porous activated biochar enriched with SO3H- as a catalyst for eco-friendly biodiesel production from the microalga Chlorella vulgaris. An extensive analysis, employing advanced techniques such as XRD, FTIR, TGA, XPS, NH3-TPD, BET, SEM-EDX, and TEM, was conducted to elucidate the physicochemical properties of BT-SO3H catalysts. The synthesized catalyst demonstrated its efficiency in converting the total lipids of Chlorella vulgaris into biodiesel, with varying concentrations of 3%, 5%, and 7%. Notably, using a 5% BT-SO3H concentration resulted in remarkably higher biodiesel production about 58.29%. Additionally, the fatty acid profile of C. vulgaris biodiesel indicated that C16:0 was the predominant fatty acid at 24.31%, followed by C18:1 (19.68%), C18:3 (11.45%), and C16:1 (7.56%). Furthermore, the biodiesel produced via 5% BT-SO3H was estimated to have higher levels of saturated fatty acids (SFAs) at 34.28%, monounsaturated fatty acids (MUFAs) at 30.70%, and polyunsaturated fatty acids (PUFAs) at 24.24%. These findings highlight the promising potential of BT-SO3H catalysts for efficient and environmentally friendly biodiesel production from microalgal species.